Development of Project Based Learning with STEAM Approach Model Integrated Science Literacy in Improving Student Learning Outcomes - Nuraini Nuraini; Indra Himayatul Asri; Nurul Fajri (Postgraduate, University of Mataram, 2023)
In preparing students who have the skills to respond to the challenges of the times and face the demands of 21st century learning, teachers need to develop students' science literacy and design learning in accordance with the characteristics and learning outcomes of students. The purpose of this study is to develop learning with PjBL with STEAM approach model integrated science literacy. Research is carried out through the stages of needs analysis, product design, product development, product implementation and evaluation. The research object was grade X students of SMAN 2 Selong totaling 35 students with 25 female students and 10 male students. Research instruments include needs analysis questionnaire guidelines, product validation guidelines, product practicality guidelines, teacher response guidelines and learning outcomes tests on ecosystem materials.Â The collected data was analyzed using descriptive analysis.Â Data analysis showed that the product developed was classified as valid with an average score of validation by 3 experts, namely linguists, material experts and learning technology experts respectively 83.91, 84.64 and 83.73.Â The product is also classified as practical with an average practicality score of 82.63. The product is classified as effective with an effectiveness percentage of 88.57%. The developed product has high potential in improving student learning outcomes on ecosystem materials with an N-Gain of 0.76